2022
DOI: 10.11591/ijece.v12i3.pp2986-2995
|View full text |Cite
|
Sign up to set email alerts
|

Modern drowsiness detection techniques: a review

Abstract: <span>According to recent statistics, drowsiness, rather than alcohol, is now responsible for one-quarter of all automobile accidents. As a result, many monitoring systems have been created to reduce and prevent such accidents. However, despite the huge amount of state-of-the-art drowsiness detection systems, it is not clear which one is the most appropriate. The following points will be discussed in this paper: Initial consideration should be given to the many sorts of existing supervised detecting tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Statistical imputation techniques such as mean and mode imputation for categorical features to maintain the integrity and efficacy of the detection model features with a high percentage of missing values can also be excluded using feature selection approaches. [16][17][18]…”
Section: Data Cleaning and Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical imputation techniques such as mean and mode imputation for categorical features to maintain the integrity and efficacy of the detection model features with a high percentage of missing values can also be excluded using feature selection approaches. [16][17][18]…”
Section: Data Cleaning and Pre-processingmentioning
confidence: 99%
“…The authors also suggest looking into how other hyperparameters, such as batch size and learning rate, affect the effectiveness of the DW-FedAvg approach. Further investigation may examine the DW-FedAvg approach's application to domains [18] other than Android malware classification to assess its efficacy in various contexts [46].…”
Section: Behavioural Analysis Modelmentioning
confidence: 99%
“…Several survey and review studies that integrated DL models with IoT devices in driver drowsiness detection systems [ 5 , 6 , 7 , 8 ] have reported that the major challenge is training the DL models, in that DL has a complex architecture and is heavyweight. The approximate range of the DL model size in the literature on driver drowsiness detection is from 10 MB to 54 MB.…”
Section: Introductionmentioning
confidence: 99%
“…And biosensors (such as electromyography (EMG) [5], as well as force sensors [6], Electroencephalography (EEG), and magnetoencephalography (MEG) have been used. Electromechanical sensors can effectively detect biological data [5], [7].…”
Section: Introductionmentioning
confidence: 99%